Molecular profiling of nematode associates with Rhynchophorus ferrugineus in southern Italy. Issue 24 (28th November 2019) - De Luca, Francesca; Fanelli, Elena; Oreste, Monica; Scarcia, Gianluca; Troccoli, Alberto; Vovlas, Alessio; Trisciuzzi, Nicola; Tarasco, Eustachio
Abstract: A survey of nematodes associated with the red palm weevil Rhynchophorus ferrugineus was conducted in southern Italy in 2015 and 2016 in order to create a species inventory and obtain data about nematode biodiversity. A total of 70 insect samples (pupae and adults) were collected from infested Phoenix canariensis, Phoenix dactylifera, and Chamaerops humilis palms in three Italian Regions: sampling took place at 11 locations in Apulia, 1 in Basilicata, and 1 in Sardinia regions. Individual insects were dissected to determine nematode presence, and different nematode species were also recovered from red palm weevil cocoons collected at the sites in Apulia. Individual nematodes were molecularly identified by sequencing the ITS, D2‐D3 expansion domains of the 28SrRNA gene and the mitochondrial COI and inferring the phylogenetic relationships. The insect‐associated nematofauna identified belonged to the families Rhabditidae, Cephalobidae, and Diplogastridae. Just two nematode species, Teratorhabditis synpapillata and Mononchoides macrospiculum, were always found in association with adult insects and cocoons taken from all sampling sites. This paper reports on the biodiversity of the nematodes associated with R. ferrugineus and on current knowledge of the specific habitat of specialized and divergent entomophilic nematodes. Abstract : The manuscript concerns the molecular identification of nematodes associated with Rhynchophorus ferrugineus by using the reverse taxonomy approach. The aim of this study was to characterize the nematofauna at level of ecological, evolutionary, and population genomics. For the first time, it has been shown that two nematode species are specifically associated with the RPW, the other species were incidentally associated to the RPW which constitute mobile microhabitat used by nematodes to feed, to move and to be transported.